Resource availability drives bacterial succession during leaf-litter decomposition in a bromeliad ecosystem. Issue 4 (16th March 2020) - Carrias, Jean-François; Gerphagnon, Mélanie; Rodríguez-Pérez, Héctor; Borrel, Guillaume; Loiseau, Camille; Corbara, Bruno; Céréghino, Régis; Mary, Isabelle; Leroy, Céline
ABSTRACT: Despite the growing number of investigations on microbial succession during the last decade, most of our knowledge on primary succession of bacteria in natural environments comes from conceptual models and/or studies of chronosequences. Successional patterns of litter-degrading bacteria remain poorly documented, especially in undisturbed environments. Here we conducted an experiment with tank bromeliads as natural freshwater microcosms to assess major trends in bacterial succession on two leaf-litter species incubated with or without animal exclusion. We used amplicon sequencing and a co-occurrence network to assess changes in bacterial community structure according to treatments. Alpha-diversity and community complexity displayed the same trends regardless of the treatments, highlighting that primary succession of detrital-bacteria is subject to resource limitation and biological interactions, much like macro-organisms. Shifts in bacterial assemblages along the succession were characterized by an increase in uncharacterized taxa and potential N-fixing bacteria, the latter being involved in positive co-occurrence between taxa. These findings support the hypothesis of interdependence between taxa as a significant niche-based process shaping bacterial communities during the advanced stage of succession. Abstract : This study details ecological succession patterns of litter-degrading bacteria in a natural environment and tests whether trends in primary succession can be predicted from niche-based concepts established for macro-organisms.